APPLICATION OF MACHINE LEARNING FOR BIG DATA ANALYSIS (Web of Technology: Multidimensional Research Journal, 2024)
The exponential growth of data in various sectors has necessitated the development of advanced analytical techniques to extract meaningful insights. Machine learning (ML), a subset of artificial intelligence, has emerged as a pivotal tool in the analysis of big data, offering robust solutions for pattern recognition, predictive analytics, and decision-making processes. This paper explores the application of machine learning algorithms in big data analysis, highlighting their ability to handle vast and complex datasets efficiently. By leveraging supervised and unsupervised learning techniques, ML models can uncover hidden patterns, classify data accurately, and predict future trends with high precision. The study delves into the integration of ML with big data technologies such as Hadoop and Spark, emphasizing the scalability and real-time processing capabilities that enhance data analysis outcomes. Furthermore, the paper examines various ML methodologies, including neural networks, support vector machines, and ensemble learning, assessing their effectiveness in different big data environments. Case studies from diverse industries such as healthcare, finance, and marketing are presented to illustrate the practical applications and benefits of ML in big data analytics. The challenges associated with implementing machine learning in big data, including data quality, computational resources, and algorithmic bias, are also discussed. Finally, the paper provides insights into future trends and potential advancements in ML-driven big data analysis, underscoring the importance of continuous innovation to address the evolving complexities of data-driven decision-making. This comprehensive analysis underscores the transformative impact of machine learning on big data, offering valuable perspectives for researchers, practitioners, and students in the field of data science and analytics.